Kamachiy'Mayistru: Adaptive module to support teaching to people with learning difficulties (2023)
Purpose 'The purpose of this paper is to propose Kamachiy-Mayistru (KM), an adaptive module to support teaching to people with learning difficulties. In Colombia, learning disabilities and difficulties are frequent in the integration classroom. Proper learning can be achieved as long as teaching strategies and didactic tools are the most adequate to the specific student characteristics and follow the suggestions given by experts for each learning difficulty. This module assists the teacher to prepare a course taking into account the disability profile, the student profile and pedagogical model suggestions. In this way, the student can learn utilizing the format and didactic tools more appropriate to their specific necessities. Design/methodology/approach'The design and implementation of the KM comprises the following phases: identify the most important student, teacher, difficulties and course parameters to take into account in the adaptation process; design the data model that supports activity adaptation, based on student characteristics and difficulties; implement the platform; and validate the approach through a case study of teachers and their students with difficulties. Findings'The application ofKMin the case study indicated the effectiveness ofKMto assist teachers in organizing course activities for students with and without disabilities or difficulties. Research limitations/implications'KM addresses specific student difficulties: attention, memory and languages. KM does not address severe cognitive disabilities. Regarding the validation, it is recommended to pursue new case studies to further demonstrate the effectiveness of the approach in a broader population. Practical implications'The main approach inKMis to suggest activities or pedagogical strategies to teachers to best support learning in students with difficulties or disabilities. The core of KM is an algorithm, called "Adapt Course", that takes as input student and disability profiles, the course contents and the pedagogical model and creates course structures that are specially tailored to each student. Social implications'This model recommends teachers different activities, based on the specific student difficulties, to create personalized courses. It is able to address specific educational issues that are associated with learning difficulties and disabilities, such as educational integration, through content organization and personalized information display, which are based on the inherent characteristics of each student in the classroom. Originality/value'It is based on a conceptual model that provides the essential architecture to design and implement virtual learning environments for students with learning difficulties or disabilities. © Emerald Group Publishing Limited.